The Mysterious and Obvious in American Diplomacy : From Monroe to Trump. - Farkhutdinov, Insur (Newcastle-upon-Tyne : Cambridge Scholars Publisher, 2020)
The book analyses the origins of the idea of interference in the internal affairs of other states and preventive strike in international law, beginning with the Monroe Doctrine (1823). American diplomacy has not changed in principle in the last two centuries, and is still based on the Monroe doctrine. This is proven here through the study of the foreign policy of the vast majority of US presidents, from Monroe to Trump. As the book shows, one of the main tools of American domination throughout the world in the second half of the 20th century and the beginning of the 21st is the doctrine of the.
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Intervention (International law); Monroe doctrine; United States -- Foreign relations; Intervention (Droit international); Doctrine de Monroe; États-Unis -- Relations extérieures.; Modern history to 20th century: c 1700 to c 1900.; History of the Americas; Politics & government; Diplomatic relations; Intervention (International law); Monroe doctrine; United States